Efeito antioxidante e antiadipogênico do extrato aquoso de alecrim (Rosmarinus officinalis l.) em células HepG2 e 3T3-L1. 2020 - Pereira, Raquel Oliveira (2020)
The species Rosmarinus officinalis L., also known as rosemary, is an aromatic herb characterized as a promising source of phenolic compounds. Among the known biological effects, the following stand out: antioxidant, anti-inflammatory and improved lipid profile. Despite biological activities already well described, the aqueous extract of rosemary (RAE), which has rosmarinic acid and apigenin as its main components, unlike the more nonpolar extracts, has not yet been explored in the context of obesity and its problems. In this sense, the objective of the present study was to evaluate the participation of EAA bioactive compounds in the prevention of alterations in lipid metabolism and oxidative stress in culture of hepatocytes (HepG2) and adipocytes (3T3-L1). For this, HepG2 cells were exposed to different concentrations of EAA (5-2000 μg / mL) in the presence or absence of palmitic acid, to assess cell viability, determine reactive oxygen species (ROS) and determine lipid incorporation. 3T3- L1 cells were also subjected to the cell viability assay after incubation for 48 hours. These cells were stimulated to differentiate into mature adipocytes, in the presence or absence of EAA. After 7 days of differentiation, 3T3-L1 cells were subjected to the same determinations used for assays with HepG2 cells. Statistical analysis was performed by analysis of variance (ANOVA) followed by the Tukey test, adopting statistically significant differences (p <0.05) between the means. The results show that EAA did not alter cell viability in HepG2 cells when compared to control, and the presence of palmitic acid did not change this condition. However, a reduction in viability was observed in the 3T3-L1 strain when exposed to EAA in all concentrations. However, the dose of 5μg / mL did not show cytotoxicity. A reduction in ROS production was also observed in HepG2 cells exposed to palmitic acid and treated with EAA (p <0.05). This reduction also occurred in differentiated 3T3-L1 cells (p <0.05), but the reduction in ROS did not alter the incorporation of lipids in hepatocytes. On the other hand, an inhibitory activity was observed at the dose of 10μg / mL of EAA in the differentiation of 3T3- L1 cells (p <0.05), quantified through a lower presence of lipid droplets in these cells. The main findings of this study show that EAA was able to change the redox state in HepG2 and 3T3-L1 culture, as well as inhibiting the differentiation of 3T3-L1 pre-adipocytes into mature adipocytes. This activity may be associated with a lower availability of ROS and less activation of adipogenesis pathways. However, the oxidative stress reduction mechanism observed in HepG2 cells is not associated with a reduction in the incorporation of lipids in HepG2, so other pathways need to be investigated.